An Arctic Paradox: Response of Fluvial Hg Inputs and Bioavailability to Global Climate Change in an Extreme Coastal Environment - Lacerda, Luiz Drude de; Marins, Rozane Valente; Dias, Francisco José da Silva (Frontiers in Earth Science, 2020)
Global climate change interacts with regional alterations of land use in coastal basins and promotes rapid changes in the biogeochemistry of the coastal zone. In tropical latitudes mangroves dominate coastal and estuarine environments and respond rapidly to these changes. The semiarid coast of Brazil, as most other semiarid environments, is being strongly affected by climate change. A major environmental response is altered hydrodynamics, generally involving decreasing continental runoff to the ocean, caused by reducing annual rainfall and damming of rivers. Also, strengthening of the marine forcing, due to heat accumulation in the South Atlantic Ocean and rising sea level, push self and coastal waters into estuaries. Basin and oceanic processes positively feedback and cause an increasing the water residence time in estuaries, saline intrusion landward, accumulation of sediments in the inner reaches of estuaries and expanding mangrove areas, particularly over the past 50 years. Expansion of mangroves means expansion of the sulfate reduction metabolism, which produces large amounts of dissolved organic carbon, characterized by high capacity of forming organo-metallic complexes. The consequences on the biogeochemistry of substances flowing from land to sea are of high environmental significance, as exemplified by mercury (Hg) behavior. Dissolved and particulate Hg concentrations and fluxes are greater from the river to the estuary than from the estuary to the sea, producing an accumulation of particulate Hg in the estuary. Particulate Hg export may occurs only during extremely rainy periods, and is eventually deposited is shelf sediments, displaying low bioavailability. Dissolved; reactive and DOC-bound Hg export is practically nonexistent during rainy periods but increases two orders of magnitude during the progressively longer dry periods. These highly bioavailable forms of Hg will end up in the lower estuary and coastal food webs, increasing contamination of the biota and human exposure to Hg.